2018
DOI: 10.1097/gox.0000000000001826
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Investigating Fistula Rate Following Primary Palatoplasty Using Acellular Dermal Matrix

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 16 publications
(26 reference statements)
2
14
2
Order By: Relevance
“…Gilardino et al in 2018 in a prospective study conducted on 130 patients undergoing primary palatoplasty stated that the incidence of stula in the study group using ADM was 1.5% versus 12.3% in the control group. The results of this study showed strong evidence of the positive effect of using ADM in the development of stula following primary palatoplasty (25) .…”
Section: Clark Et Al In 2003supporting
confidence: 51%
See 1 more Smart Citation
“…Gilardino et al in 2018 in a prospective study conducted on 130 patients undergoing primary palatoplasty stated that the incidence of stula in the study group using ADM was 1.5% versus 12.3% in the control group. The results of this study showed strong evidence of the positive effect of using ADM in the development of stula following primary palatoplasty (25) .…”
Section: Clark Et Al In 2003supporting
confidence: 51%
“…In addition, in few previous studies generalized results have not been reported due to small sample size. Therefore, there is a need for further studies (25). The present study was designed to investigate the usage and effect of alloderm in the early stages of palatoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…This consists of (1) relaxing incisions, (2) a complete intravelar veloplasty, (3) “total release” of the tensor aponeurosis at the level of the hamulus, and (4) circumferential dissection and controlled stretching of the greater palatine neurovascular bundle. Based on a recent prospective clinical trial (Gilardino et al, 2018), there is a clinically significant reduction in fistula formation with the routine use of ADM in primary cleft palate repairs.…”
Section: Discussionmentioning
confidence: 99%
“…That local pathogen-related infections may be partly responsible for oronasal fistulae formation supports the former. Other reported methods to protect the palate post-repair include applying acrylic obturators (Bowers and Gruber, 1973) or reinforcing the repair with acellular dermal matrix (Losee and Smith, 2011;Gilardino et al, 2018).…”
Section: Adjunctive Measuresmentioning
confidence: 99%